Comprehensive power loss analysis for hybrid distribution transformer - Zixia Sang; Xu Zheng; He Lei; Jiong Yan; Jie Cai; Rengcun Fang (AIP Advances)
Compared with traditional power transformers, Hybrid Distribution Transformers (HDTs) generate higher power losses due to the application of power electronic converters. However, HDTs can apply reactive power compensation as well as three-phase load current unbalance compensation, which leads to line loss reduction of the distribution power grid. When comparing the power losses of HDTs and traditional transformers, it is necessary to comprehensively consider the operational power loss of HDTs and line losses of the distribution network reduced by its converter. This article proposes a comprehensive loss model for the application of HDTs in distribution networks and conducts theoretical calculations on HDT self-losses and distribution network line losses caused by reactive power and three-phase asymmetric load currents. The power losses on the transmission wire of the distribution power grid with the application of HDTs instead of traditional transformers are analyzed. The calculation and simulation results based on parameters such as reactive power, three-phase unbalanced current, and HDT comprehensive loss have verified the correctness of the theoretical analysis.